Chlamydia trachomatis and Neisseria gonorrhoeae PCR detection in women treated for ectopic pregnancy - Racková, Jana; Záhumenský, Jozef; Zikán, Michael; Menzlová, Erika; Sehnal, Borek (Journal of obstetrics and gynaecology, 2022)
The aim of this study was to determine the presence of Chlamydia trachomatis (ChT) and Neisseria gonorrhoae (NG) in the genital tract of women with ectopic pregnancy and to compare the positive results with patients' self-reported history of PID. Overall 40 women were eligible for the study. The samples for the ChT and NG Polymerase Chain-reaction (PCR) detection were obtained from the cervix, endometrium and fallopian tube. The results of testing for NG at all sites were negative as were the results from cervical testing for ChT. The prevalence of ChT in the upper genital tract was 12.5%. No statistically significant correlation was found between the positive cases and the previous signs of PID and laparoscopic findings. We found statistically significant relationship between signs of pelvic inflammation in a pacients' history and histopathological findings of tubal inflammation. 12.5% prevalence of ChT confirms the ascending genital infection. There was no association between the positive PCR result and clinical history of pelvic inflammation.IMPACT STATEMENTWhat is already known on this subject? Pelvic inflammatory disease, Chlamydia trachomatis and Neisseria gonorrhoae infections are the main risks for ectopic pregnancy. Clinical history of PID and perioperative adhesions may suggest prior upper genital infection.What do the results of this study add?Chlamydia trachomatis positive PCR result can be found in the upper genital tract without the positivity of cervical smear in women with ectopic pregnancy. Our study is unique in assessing the endometrial biopsy for the presence of Chlamydia trachomatis and Neisseria gonorrhoae.What are the implications of these findings for future clinical practice and/or future clinical research? There is no statistically significant association between positive PCR result and clinical history of PID or pelvic adhesions found during laparoscopy for tubal pregnancy. Therefore there is no need for the preventive antibiotic treatment in patients with these findings.
Keywords: ženské pohlaví; polymerázová řetězová reakce; těhotenství; mimoděložní těhotenství; Female; zánět; chlamydiové infekce; lidé; Chlamydia Infections; Neisseria gonorrhoeae; Pelvic Inflammatory Disease; pánevní zánět; Pregnancy, Ectopic; Humans; Chlamydia trachomatis; Polymerase Chain Reaction; Inflammation; Pregnancy